2023
DOI: 10.1021/acsptsci.3c00047
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA-Based Therapeutics and Vaccines: What’s beyond COVID-19?

Abstract: With the rapid success in the development of mRNA vaccines against COVID-19 and with a number of mRNAbased drugs ahead in the pipelines, mRNA has catapulted to the forefront of drug research, demonstrating its substantial effectiveness against a broad range of diseases. As the recent global pandemic gradually fades, we cannot stop thinking about what the world has gained: the realization and validation of the power of mRNA in modern medicine. A significant amount of research has now been concentrated on develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Given global temperatures rise, melting glaciers releasing old pathogens or the increasing transmission of pathogens from animals to humans, the danger of new diseases emerging is high ( Alempic et al, 2023 ). Therapeutic mRNA molecule has brought new hope, as its production process is quick and easily adjustable for many different therapeutic applications ( Li et al, 2023 ; Yu et al, 2023 ). By changing the sequence, any protein of therapeutic interest can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Given global temperatures rise, melting glaciers releasing old pathogens or the increasing transmission of pathogens from animals to humans, the danger of new diseases emerging is high ( Alempic et al, 2023 ). Therapeutic mRNA molecule has brought new hope, as its production process is quick and easily adjustable for many different therapeutic applications ( Li et al, 2023 ; Yu et al, 2023 ). By changing the sequence, any protein of therapeutic interest can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent circulating SARS-CoV-2 Spike was recently proposed to be causative of the COVID-19 associated syndrome termed PASC (post-acute sequelae of COVID-19) [25,26]. Considering that the anti-SARS vaccination campaigns are expected to be still ongoing for the next coming years [5], extensive analysis of SARS-CoV-2 Spike in ex vivo cellular systems is required for understanding possible impacts on vaccination [79].…”
Section: Discussionmentioning
confidence: 99%
“…It must be kept in mind that vaccines’ immunogenicity (including those against COVID-19) is affected by various factors. It was shown that the following factors might contribute to different vaccine responses in different regions: (i) age—infants do not have a mature immune system and therefore their cell-mediated immune responses are very weak, aging may lead to immune-depression and inflammations and a high prevalence of comorbidities, and in aged patients, immunogenicity is lower; (ii) poor diet and malnutrition and composition of gut microflora—immune responses to vaccination is weaker in low- and middle-income countries in comparison to high-income ones; (iii) it was shown that humoral responses after vaccination against COVID-19 were weaker in obese people; (iv) immunogenicity also varies between males and females (women usually have higher immune responses), which can lead to differences in responses to vaccine; and (v) some studies suggest that host genetics also may contribute to vaccination outcomes [ 89 ]. Table 3 shows a comparison of inactivated vaccines’ efficacy as an example.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%